Mały człowiek sukcesu, czyli o roli przedszkola w przebiegu kariery edukacyjnej dzieci - Mironiuk-Netreba, Alicja (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
In the beginning of the 21st century the issue of proper kindergarten education is very popular in both, European and Polish, public debates. It is caused by a significant influence, which high quality education of small children has on their future academic and professional career. However, the quality in education not only refers to sufficient number of care facilities, but rather to valuable, full-day learning program, work of well-trained teachers and kindergarten-community partnership. In result, children who attend to high quality kindergarten education evince high self- esteem, curiosity, endurance and independence in performing academic tasks all these skills are indispensable in the process of life-long learning. Other positive effects of attending to kindergartenare: school readiness, higher rates of high school graduation, reduction of grade repetition, and number of children placed in special education, more stable financial and family life in future, reduction of crime, promotion of healthy lifestyle. What is more, positive effects of kindergarten education are more significant to children with disadvantaged social background.
Keywords: edukacja przedszkolna; gotowość szkolna; rozwój małego dziecka; sukces edukacyjny; wyrównywanie szans